Plant-Produced Chimeric VHH-sIgA Against Enterohemorrhagic E. coli Intimin Shows Cross-Serotype Inhibition of Bacterial Adhesion to Epithelial Cells - Saberianfar, Reza; Chin-Fatt, Adam; Scott, Andrew; Henry, Kevin A.; Topp, Edward; Menassa, Rima (Frontiers in Plant Science, 2019)
Enterohemorrhagic Escherichia coli (EHEC) has consistently been one of the foremost foodborne pathogen threats worldwide based on the past thirty years of surveillance. EHEC primarily colonizes the bovine gastrointestinal (GI) tract from which it can be transmitted to nearby farm environments and remain viable for months. There is an urgent need for effective and easily implemented pre-harvest interventions to curtail EHEC contamination of the food and water supply. In an effort to address this problem, we isolated single-domain antibodies (VHHs) specific for intimin, an EHEC adhesin required for colonization, and designed chimeric VHH fusions with secretory IgA functionality intended for passive immunotherapy at the mucosal GI surface. The antibodies were produced in leaves of Nicotiana benthamiana with production levels ranging between 1–3% of total soluble protein. In vivo assembly of all subunits into a hetero-multimeric complex was verified by co-immunoprecipitation. Analysis of multivalent protection across the most prevalent EHEC strains identified one candidate antibody, VHH10-IgA, that binds O145:Hnm, O111:Hnm, O26:H11 and O157:H7. Fluorometric and microscopic analysis also indicated that VHH10-IgA completely neutralizes the capacity of the latter three strains to adhere to epithelial cells in vitro. This study provides proof of concept that a plant-produced chimeric secretory IgA can confer cross-serotype inhibition of bacterial adhesion to epithelial cells.